2014
DOI: 10.1155/2014/367493
|View full text |Cite
|
Sign up to set email alerts
|

Near-Peer Teaching and Exam Results: The Acceptability, Impact, and Assessment Outcomes of a Novel Biological Sciences Revision Programme Taught by Senior Medical Students

Abstract: Background. Near-peer teaching is becoming increasingly popular as a learning methodology. We report the development of a novel near-peer biological sciences revision course and its acceptability and impact on student confidence and exam performance. Methods. A cross-sectional analysis of tutee-completed evaluation forms before and after each session was performed, providing demographic details, quality scores, and self-rating of confidence in the topic taught on a 0 to 100 mm visual analogue scale (VAS). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…10 Preparation for the OSCE is usually via senior clinician teaching; however, another approach is near-peer teaching (NPT), which refers to senior medical students teaching more junior students. 11 Recent studies have reported that NPT-style revision sessions can play a significant role in alleviating this stress, attesting to its use in medical education. 10 12 13…”
Section: Introductionmentioning
confidence: 99%
“…10 Preparation for the OSCE is usually via senior clinician teaching; however, another approach is near-peer teaching (NPT), which refers to senior medical students teaching more junior students. 11 Recent studies have reported that NPT-style revision sessions can play a significant role in alleviating this stress, attesting to its use in medical education. 10 12 13…”
Section: Introductionmentioning
confidence: 99%